High-intensity exercise training abrogates age differences in spomatotropic hormone concentrations - Sellami, M.; Ben Abderahmen, A.; Hayes, L. D.; Kebsi, W.; Zouhal, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Aim: The aim of this investigation was to compare systemic concentrations of growth hormone (GH), Insulin-like growth factor 1 (IGF-1), and Insulin-like growth factor-binding protein (IGFBP-3) in response to a combined sprint and strength training program in young and middle-aged men. Methods: Thirty-eight healthy, moderately trained men participated in this study. Young and middle-aged men were randomly assigned into two experimental conditions (training or control). A young training group (21.4±1.2yrs, YT, n=10), a young control group (21.3±1.3yrs, YC, n=9), a middle-aged training group (40.4±2.1 yrs, MAT, n=10) and a middle-aged control group (40.3±1.7 yrs, MAC, n=9) were assessed before (P1), and after (P2) a high-intensity sprint and strength training program (HISST) for 13 weeks (4 times/week). At P1 and P2, maximal oxygen uptake (VO2max) and maximal anaerobic power was assessed using the Wingate Anaerobic Test (WAnT). Blood samples were collected at rest, after warm-up (50% VO2max), immediately post-, and 10 min post-WAnT. Results: Resting serum GH, IGF-1, and IGFBP-3 increased significantly (p<0.05) after HISST in MAT. This increase approached values to those of YT after HISST. In response to warm-up and the WAnT, GH andIGF-1levels increased significantly (p<0.05) in YT and MAT after HISST. VO2max and maximal anaerobic power increased (p<0.05) after HISST in both YT and MAT compared to YC and MAC. Conclusion: These data suggest combined sprint and strength training improves muscle power, VO2max, and increases activity of the GH/IGF-1axis. Moreover, GH/IGF-1axis sensitivity to a WAnT in middle-aged men was additionally increased. However, the causal of these hormonal adaptations remains to be clarified.